Germanium-on-carborundum surface phonon-polariton infrared metamaterial - Qiang, Bo (2021)
Surface phonon-polaritons in thin layers of high-index dielectric structures are emerging as promising excitations for exploitation in high-density photonic devices. Here, a mid-infrared phononic–dielectric metamaterial, a 2D periodic array of germanium discs on silicon carbide (carborundum) is demonstrated. It is shown that the metamaterial can support sharp resonances at the free space wavelength that is at least ten times larger than lattice parameter of the array. With germanium discs of thickness 120 nm and diameter 1 µm, a metamaterial resonance at the wavelength of 11 µm is observed. A blueshift of the resonant frequency observed upon increase of the disk size is related to the anomalous dispersion of surface polaritons at germanium carborundum interface. It is argued that such surface phonon-polariton metamaterial is a promising platform for applications where enhanced homogeneity of optical response is required, such as imaging, holography, and cloaking.